2019
DOI: 10.1007/s00421-019-04160-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory coordination reveals training-specific physiological adaptations

Abstract: Author post-print (accepted) deposited by Coventry University's Repository

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 37 publications
(44 reference statements)
2
28
0
Order By: Relevance
“…For instance, the analysis of continuous variables throughout a training process beyond maximal values could provide more sensitive information to determine specific adaptations in different training programs. This has been recently demonstrated by Garcia-Retortillo et al (2019), who compared HIIT and MICT programs and observed that, despite improving markers of aerobic fitness to a similar extent, changes in cardiorespiratory coordination were specific for each training intervention. For endurance recreational runners, moderate continuous training with extensive aerobic loads is the most frequently used type of training (see for example, Fokkema et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
“…For instance, the analysis of continuous variables throughout a training process beyond maximal values could provide more sensitive information to determine specific adaptations in different training programs. This has been recently demonstrated by Garcia-Retortillo et al (2019), who compared HIIT and MICT programs and observed that, despite improving markers of aerobic fitness to a similar extent, changes in cardiorespiratory coordination were specific for each training intervention. For endurance recreational runners, moderate continuous training with extensive aerobic loads is the most frequently used type of training (see for example, Fokkema et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
“…Candidate physiological explanations for these results could include localized tissues or specific subsystems. Certainly, heightened activity by sympathetic nervous system can increase change covariation among disparate physiological systems (e.g., Garcia-Retortillo et al, 2019). Expectation might provoke stress, anxiety, and uncertainty.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the studies reviewed above, which did not use this technique to explore cardiorespiratory function, are unable to provide information on co-variations of the cardiovascular and respiratory systems. As suggested by the authors of references [76,77,79], using the cardiorespiratory coordination approach should be more sensitive to training effects than the traditional aerobic physiological markers, and thus could be advantageously used in cross-sectional and longitudinal protocols. Despite this, its feasibility and validity for use in older populations must be demonstrated first.…”
Section: Cardiorespiratory Hypothesis and Cognitive Declinementioning
confidence: 99%